PMIPv6 integrated with MIH for flow mobility management: a real testbed with simultaneous multi-access in heterogeneous mobile networks - Alves, H.; Silva, L. M.; Marinheiro, R. N.; Moura, J. A. R. S. (Wireless Personal Communications, 2017)
The exponential growth of the number of multihomed mobile devices is changing the way how we can connect to the Internet. Our mobile devices are demanding for more network resources, in terms of traffic volume and QoS requirements. Unfortunately, it is very hard for a multihomed device to be simultaneously connected to the network through multiple links. The current work enhances the network access of multihomed devices, agnostically to the deployed access technologies. This enhancement is achieved by using simultaneously all of the mobile devices interfaces, and by routing each individual data flow through the most convenient access technology. The proposed solution is only deployed at the network side and it extends Proxy Mobile IPv6 with flow mobility in a completely transparent way to mobile nodes. In fact, it gives particular attention to the handover mechanisms, by improving the detection and attachment of nodes in the network, with the inclusion of the IEEE 802.21 standard in the solution. This provides the necessary implementation and integration details to extend a network topology with femtocell devices. Each femtocell is equipped with various network interfaces, supporting a diverse set of access technologies. There is also a decision entity that individually manages each data flow according to its QoS requisites. The proposed solution has been developed and extensively tested with a real prototype. Evaluation results evidence that the overhead for using the solution is negligible as compared to the offered advantages such as: the support of flow mobility, the fulfil of VoIP functional requisites, the session continuity in spite of flows mobility, its low overhead, its high scalability, and the complete transparency of the proposed solution to user terminals.